Assessment of genetically modified cotton 281‐24‐236 × 3006‐210‐23 for renewal authorisation under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐RX‐019). (10th November 2022) - ,; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: Following the submission of application EFSA‐GMO‐RX‐019 under Regulation (EC) No 1829/2003 from Corteva Agriscience LLC represented by Corteva Agriscience Belgium B.V., the Panel on Genetically Modified Organisms of the European Food Safety Authority was asked to deliver a scientific risk assessment on the data submitted in the context of the renewal of authorisation application for the insect resistant genetically modified cotton 281‐24‐236 × 3006‐210‐23, for food and feed uses, excluding cultivation within the European Union. The data received in the context of this renewal application contained post‐market environmental monitoring reports, a systematic search and evaluation of literature, updated bioinformatic analyses, and additional documents or studies performed by or on behalf of the applicant. The GMO Panel assessed these data for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the context of the original application. The GMO Panel concludes that there is no evidence in renewal application EFSA‐GMO‐RX‐019 for new hazards, modified exposure or scientific uncertainties that would change the conclusions of the original risk assessment on cotton 281‐24‐236 × 3006‐210‐23.